K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(0,5x-75\%x=\left(\frac{1}{3}-1\right)^2\)

\(\Leftrightarrow\frac{1}{2}x-\frac{3}{4}x=\left(-\frac{2}{3}\right)^2\)

\(\Leftrightarrow-\frac{1}{4}x=\frac{4}{9}\)

\(\Leftrightarrow x=-\frac{16}{9}\)

\(0,5x-75\%x=\left(\frac{1}{3}-1\right)^2\)

\(< =>\frac{1}{2}x-\frac{3}{4}x=\left(-\frac{2}{3}\right)^2\)

\(< =>-\frac{1}{4}x=\frac{4}{9}\)

\(=>x=\frac{-16}{9}\)

20 tháng 4 2024

Bài 1:

0,5\(x\) - \(\dfrac{2}{3}\)\(x\) = \(\dfrac{7}{12}\)  

\(\dfrac{1}{2}\)\(x\) - \(\dfrac{2}{3}x\)  = \(\dfrac{7}{12}\)

(\(\dfrac{1}{2}-\dfrac{2}{3}\))\(x\) = \(\dfrac{7}{12}\)

\(\dfrac{1}{6}\)\(x\)         = \(\dfrac{7}{12}\)

     \(x\)         = \(\dfrac{7}{12}\) : (- \(\dfrac{1}{6}\))

     \(x\)        = - \(\dfrac{7}{2}\)

Vậy \(x\) = - \(\dfrac{7}{2}\)

 

 

a: =>3/2x=64/15

=>x=128/45

b: =>-1/6x=7/12

=>x=-7/2

c: =>11/2*x=1/2

=>x=1/2:11/2=1/11

12 tháng 6 2017

\(\frac{x+1}{2x+1}=\frac{0,5x+2}{x+3}\)ĐKXĐ: \(x\ne-\frac{1}{2};x\ne-3\)

\(\Rightarrow\left(x+1\right)\left(x+3\right)=\left(2x+1\right)\left(0,5x+2\right)\)

\(\Leftrightarrow x^2+x+3x+3=x^2+0,5x+4x+2\)

\(\Leftrightarrow x^2+4x+3=x^2+4,5x+2\)

\(\Leftrightarrow x^2-x^2+4x-4,5x=2-3\)

\(\Leftrightarrow-0,5x=-1\)

\(\Leftrightarrow x=2\)

vậy x=2

2 tháng 5 2015

a.x=3

b.x=-21/2

c.-7/2

d.112/81

1 tháng 6 2016

0,5x-2/3(x-1)=1/6

1/2x-(2/3x-2/3)=1/6

1/2x-2/3x+2/3=1/6

x.(1/2-2/3)=1/6-2/3

x.(-1/6)=-1/2

x.(-1/6)=-1/2

x=-1/2:(-1/6)

x=-1/2.(-6)

x=3

Vậy x=3

2 tháng 6 2016

 cảm ơn bạn nhiều nhé